The transformation of the socialist party and others chilean left sectors - Corvalán Márquez, Luis (Cuadernos Latinoamericanos, 2018)
This article proposes an interpretation about the process called “renovation” inside the Chilean Socialist Party and others sectors of the Chilean left. It aims to argue about the experience of the aforementioned political entities since the end of the 1970s, under the impact of the September 11th defeat, in which the European Social Democracy played an important role. The methodology used to demonstrate this hypothesis consists in developing a historical review procedure of the political and ideological trajectory followed by the Socialist Party from its origins and onwards in order to visualize the rupture, carried out by the “renovation” and supported by the European Social Democracy. The main conclusion obtained by this procedure was that more than a renewal, the Socialist Party experienced an identity change.